1998
DOI: 10.1046/j.1440-1770.1998.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Grazing by a resident macrozooplankton community and non‐resident Daphnia carinata King: A preliminary in situ incubation study

Abstract: A 24 h incubation study was conducted in situ in Manly Dam reservoir, Sydney, Australia. The study aimed to evaluate the relative effectiveness of grazing on phytoplankton by a resident macrozooplankton community, dominated by the cladoceran Ceriodaphnia and some copepods, in comparison with grazing by added, non-resident Daphnia carinata in the absence of the resident macrozooplankton community. Although there was some variability in the measured grazing rates among incubation bottles (volume: 1.28 L), D. car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition, D. carinata is able to feed on cyanobacteria (Kobayashi, 1993) while being resistant to certain cyanobacterial toxins (Matveev et al, 1994b). Kobayashi et al (1998) found that the weight specific clearance rate of D. carinata was between two and 65 times higher (0.27-3.83 l mgdw )1 d )1 ) than that of the resident zooplankton community in a reservoir in Sydney. This suggests that D. carinata is effective at reducing phytoplankton where planktivorous fish are absent or occur in low numbers and where phytoplankton production is sufficiently high to sustain large D. carinata populations (see also Burns, 1998).…”
Section: Food Chain Interactions -Biomanipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, D. carinata is able to feed on cyanobacteria (Kobayashi, 1993) while being resistant to certain cyanobacterial toxins (Matveev et al, 1994b). Kobayashi et al (1998) found that the weight specific clearance rate of D. carinata was between two and 65 times higher (0.27-3.83 l mgdw )1 d )1 ) than that of the resident zooplankton community in a reservoir in Sydney. This suggests that D. carinata is effective at reducing phytoplankton where planktivorous fish are absent or occur in low numbers and where phytoplankton production is sufficiently high to sustain large D. carinata populations (see also Burns, 1998).…”
Section: Food Chain Interactions -Biomanipulationmentioning
confidence: 99%
“…There are now a number of studies from Australia that show the potential for zooplankton grazers to control phytoplankton. In particular, it has been shown that Daphnia carinata, a large cladoceran, can be present in high densities in Australian systems (Mitchell & Williams, 1982) and that it effectively grazes phytoplankton (e.g., Ganf & Shiel, 1985;Merrick & Ganf, 1988;King & Shiel, 1993;Kobayashi, 1993;Kobayashi et al, 1996Kobayashi et al, , 1998Matveev & Matveeva, 1997). In addition, D. carinata is able to feed on cyanobacteria (Kobayashi, 1993) while being resistant to certain cyanobacterial toxins (Matveev et al, 1994b).…”
Section: Food Chain Interactions -Biomanipulationmentioning
confidence: 99%
“…Although traditional biomanipulation method has been successful in many applications, it is not applicable in the eutrophic lakes with algal blooms because the high concentration and large size of algae would inhibit the predation of zooplankton [49] . This technique would be limited in eutrophic lakes [50,51] . Aiming at the severe problem of algal bloom in eutrophic lakes in China, Chinese scientists suggested the non-traditional biomanipulation to reduce the algal biomass by growing planktivores fish such as silver Carp and bighead Carp [52] .…”
Section: Mechanism and Biomanipulation Control Of Algal Bloom In Eutrmentioning
confidence: 99%